Rancang Bangun Content Management System Pada Website Riset Fakultas Teknik Universitas Nurtanio Menggunakan Bahasa Pemrograman PHP Dan MySQL - Ali, Abdul Latif; Satyawan, Arief Suryadi; Wulandari, Ike Yuni; Puspita, Heni (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2022)
The development of information and communication technology has had a major impact on human life along with the easier it is to obtain information through the internet. The need for the internet is very high, especially in the world of education and especially universities. The emergence of internet technology that exists today has become a tool used to ease human work, especially in the field of websites. Website is a form of implementation of a programming language. Hypertext Preprocessor (PHP) is a web-based programming language that has the ability to process and process website data that is run by the MySQL server as a database. One that can be used for dynamic website creation is content management system (CMS) technology. This website design aims to make it easier for admin managers and kontributors to provide more interactive information to research students and lecturers in developing an autonomous electric vehicle website. This study uses a system development method in the form of a Software Development Life Cycle (SDLC) with a prototype model, namely software development in the form of a physical system work model and functions as an initial version of the system. In testing the CMS using black-box testing with boundary value analysis techniques that focus on input and output data. Based on the research and testing process that has been carried out successfully, the CMS dashboard page on the engineering faculty research website is able to process data dynamically and provide convenience for admin managers and kontributors in the development of autonomous electric vehicles.